Optimization of Supervision and Protection of Indonesian Migrant Workers (PMI) in East Java Province by UPT for Manpower Service and Protection (P2TK) of the East Java Province Department of Manpower and Transmigration - Dini Indah Aprilia; Binti Azizatun Nafi’ah, S.IAN., MPA2 (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Supervision and protection of Indonesian migrant workers is a crucial issue in ensuring their security, welfare, and rights, both during the placement process and while working abroad. Optimizing supervision and protection for Indonesian Migrant Workers is a strategic step in ensuring workers' rights are fulfilled and preventing exploitation. UPT P2TK of the East Java Provincial Department of Manpower and Transmigration plays a strategic role in providing integrated supervision and protection services. This article discusses the efforts made by UPT P2TK of the East Java Provincial Department of Manpower and Transmigration to optimize supervision and protection for migrant workers. This study uses a qualitative descriptive approach. Data collection techniques used include direct observation and interviews. The theory used is optimization theory with three indicators from Hotniar Siringoringo (2005), namely objectives, decision alternatives, and limiting resources. This article provides strategic recommendations to improve the service quality of UPT P2TK of the East Java Provincial Department of Manpower and Transmigration in order to create a more responsive and adaptive labor protection system in East Java Province. Keywords: Indonesian Migrant Workers, Optimization, Supervision and Protection.